Digital archiving system for accounting student association: enhancing continuity and efficiency in student organizations - Khalid, Muhammad Khusairi; Khairulnizam, Arisya Khadija; Khairol Anuar, Izz Danish; Nik Hazim, Nik Nurul Aina; Razak, Syuhaila (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Student association usually experience a breakdown of continuity, due to frequent changes in the positions of leadership members. Important documents and records are often mislaid or never seen by future committees, and inefficiencies revolve around the duplication of work. This project introduces a Digital Archiving System for all the student clubs, especially the accounting student association, to consolidate essential documents and preserve them. The system uses a cloud drive to store proposals, reports, committees, financial records, photographs, and any other file that should be relevant. The establishment of structured folders and naming conventions allows easy access and transferability between committees with security. This innovation further enhances transparency, facilitates customer-oriented decision-making by student leaders, and nurtures a culture of information sharing. The project is demonstrating the need for digital solutions in student governance and will form a replicable case model for all other clubs in the universities.